RESEARCH-LED HIGHER EDUCATION AND 'THE BIGGER PICTURE' - Şerban PROCHEŞ; Cecile GERWEL PROCHEŞ (Studia Universitatis Babes-Bolyai, 2015)
There is increasing pressure on higher education institutions to be research-driven and consequently populated by individuals whose main strength is research. It has already been established that the skills necessary to make a good researcher are not the same with those that make a good teacher. There are, however, other implications with respect to how teaching content is structured in terms of breadth and depth, and how breadth and depth of knowledge in turn may affect students' knowledge in their field - but also broader world views. The aim of this paper is to examine how conflict may arise from the concurrent pursuit of these goals. This discussion is based within the context of split-brain theory (breadth being a right hemisphere attribute, and depth added primarily by the left hemisphere), and highlights the potential of this theory in enhancing the higher education experience. ZUSAMMENFASSUNG. Der Druck auf die Hochschulen forschungsorientiert und somit von Personen getragen zu sein, deren Hauptstärke die Forschung ist, steigt. Es wurde bereits festgestellt, dass die Fähigkeiten, die erforderlich sind, um ein guter Forscher zu sein nicht die gleichen sind, wie die,  ein guter Lehrer zu sein. Es gibt aber auch Auswirkungen bezüglich der Breite und Tiefe der Lehrinhalte und darauf, wie die Breite und Tiefe des Wissens sowohl das Wissen der Schüler in ihrem Bereich, als auch die weitere Weltanschauungen beeinflussen. Diese Abhandlung untersucht, wie sich Konflikte aus der gleichzeitigen Verfolgung dieser Ziele ergeben können. Die Diskussion basiert auf der Split-Brain-Theorie (Breite als ein Attribut der rechten Gehirnhälfte und Tiefe wird in erster Linie von der linken Gehirnhälfte beeinflusst), und weist auf das Potential dieser Theorie hin, zur Verbesserung der Erfahrung an Hochschulen beizutragen. Schlüsselwörter: Breite der Forschungsinteressen, Hochschulbildung, Split-Brain-Theorie, Weltanschauung.